1986
DOI: 10.1161/01.hyp.8.9.810
|View full text |Cite
|
Sign up to set email alerts
|

Noncardiogenic pulmonary edema as the sole manifestation of pheochromocytoma.

Abstract: SUMMARY A 40-year-old man was admitted to the hospital with pulmonary edema without signs of left ventricular failure. Noncardiogenic pulmonary edema was diagnosed, and a subsequent workup identified a pheochromocytoma as the cause of this condition. The clinical picture could be mimicked by infusion of exogenous norepinephrine. It is concluded that surges of catecholamines from a pheochromocytoma may provoke pulmonary edema in a manner similar to that by which neurogenic pulmonary edema related to cerebral di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 8 publications
1
43
0
3
Order By: Relevance
“…Although hypotension was thought to occur only in patients with predominantly epinephrine-secreting tumors [29,30], it has also been described in norepinephrine-secreting tumors [31]. The mechanisms that lead to hypotension and shock in patients with pheochromocytoma are not understood.…”
Section: Shock and Hypotensionmentioning
confidence: 99%
“…Although hypotension was thought to occur only in patients with predominantly epinephrine-secreting tumors [29,30], it has also been described in norepinephrine-secreting tumors [31]. The mechanisms that lead to hypotension and shock in patients with pheochromocytoma are not understood.…”
Section: Shock and Hypotensionmentioning
confidence: 99%
“…Pulmonary edema as the first presentation of pheochromocytoma is uncommon and usually rapidly fatal (7,8). It can be seen not only during the course of the disease, but also after tumor resection (9).…”
mentioning
confidence: 99%
“…In most pheochromocytoma patients pulmonary edema is cardiogenic in origin. Nonetheless, noncardiogenic pulmonary edema is also seen (7). It is thought to occur as a result of catecholamine-induced transient increase in pulmonary capillary pressure due to pulmonary venoconstriction and altered pulmonary capillary permeability (10).…”
mentioning
confidence: 99%
“…Pulmonary edema as the first sign of MEN 2B is uncommon, although some reports have suggested a relationship between pulmonary edema and pheochromocytoma. Pulmonary edema as the first presentation of pheochromocytoma is rare and usually rapidly fatal [5,6]. In most pheochromocytoma patients, pulmonary edema is cardiogenic in origin, because marked catecholamine release from the tumor may cause cardiovascular emergencies, such as hypertensive crisis, myocarditis, cardiomyopathy, and myocardial ischemia [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that a rise in the pulmonary-capillary hydrostatic pressure result from postcapillary venoconstriction secondary to local effects of catecholamines and cause upstream transudation of fluid in the alveoli of interstitial space in animal study [9]. Increased permeability of the alveolocapillary membrane secondary to an elevation in catecholamines has been invoked [5]. It was shown that catecholamines dramatically increase after a variety of central nervous system insults [10].…”
Section: Discussionmentioning
confidence: 99%